From industry to greenery: exploring how users experience the Regent’s Canal - Woolf, Yarden; Short, Michael (Frontiers in Sustainable Cities, 2025)
Spending time in public places is positively associated with physical and mental health, nature connectedness and pro-environmental behavior. This is particularly important, with the ongoing climate crisis and biodiversity loss. However, many barriers exist which prevent people from accessing and experiencing greenspaces. Considering the importance of public places for sustainability, research should focus on how people experience public places, to better design them and encourage use. This study, therefore, explores how users experience the Regent’s Canal in London, as an example of a successful public place. However, there are ongoing debates regarding the definition of experience and which spatial attributes of public places shape and affect it. To address this, the current study proposes a multidimensional definition of experience and applies it to a single case study of the Regent’s Canal. Observation and walking interviews are adopted as research methods to collect qualitative data about how users experience the canal and how that spatial attributes of the canal shapes their experiences. Findings reveal that the canal’s spatial attributes have a significant impact on the way users experience it and that the canal is a successful and flexible public place that transforms from a transportation route during weekdays to a vibrant recreational place on weekends. Also, the spatial attributes of the Regent’s Canal demonstrate the complexity of experience and the need to research it from an individual perspective, contributing to current debates in the literature.